'Inah as a mode of financing: An analysis of its validity and viability from an Islamic legal perspective - Sadique, Muhammad Abdurrahman; Ansari, Abdul Haseeb (Serials Publications New Delhi, 2017)
The validity of banking transactions based on īnah remains a hotly contested issue by Islamic scholars the world over. While many of them consider such financing essentially similar to that of conventional banks, those involved in the practice produce in their defence the recognition of the legal validity of īnah by jurists of the Shāfi'i school. Imām al-Shāfi'i has generally upheld the validity of sales inclusive of a similar transaction in his famous al-Umm without referring to the term īnah. Other jurists of his school have referred to it by using this term and have upheld its validity in some of its forms, frequently categorising it under offensive types of sale. Critics contest the appropriateness of adhering to the position upheld by Shāfi'i jurists in the context of today’s bank financing where this could be an easy means of dealing in interest, and refute the possibility of the conditions necessitated for the permissibility of īnah even under that school being realisable in a banking facility. The discussion of īnah in this paper attempts to analyse the nature of the transaction referred to as īnah according to different schools of Islamic law and their ruling on īnah and related transactions, scrutinising the arguments for and against the validity of īnah. It examines the nature of recognition awarded to īnah by the Shāfi i jurists, and explores whether īnah as conceived by Shāfi'i jurists is suitable for adoption as a mode of financing by Islamic banks.